2006
DOI: 10.1149/1.2349357
|View full text |Cite
|
Sign up to set email alerts
|

A Tribochemical Study of Ceria-Silica Interactions for CMP

Abstract: Shallow trench isolation ͑STI͒ allows tighter device packing and reduced chip area for isolation. STI is critically dependent on the global planarity that is only possible using chemical mechanical polishing ͑CMP͒. Ceria-based slurries are considered the most promising candidates for STI CMP. Despite decades of use in glass polishing, the unique characteristics of ceria slurries are not well understood. In this study, we have conducted force measurements and tribological tests using an atomic force microscope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 17 publications
1
41
0
Order By: Relevance
“…Similar oxide RRs were reported in our earlier publication [13,14]. The decrease in the oxide RRs from pH 2 to 4 is presumably due to the increase in the electrostatic repulsion between the negatively charged silica abrasives and the oxide surface [15] while the increase in the oxide RRs at higher basic pH values can be attributed to an increase in oxide solubility [16].…”
Section: Resultssupporting
confidence: 88%
“…Similar oxide RRs were reported in our earlier publication [13,14]. The decrease in the oxide RRs from pH 2 to 4 is presumably due to the increase in the electrostatic repulsion between the negatively charged silica abrasives and the oxide surface [15] while the increase in the oxide RRs at higher basic pH values can be attributed to an increase in oxide solubility [16].…”
Section: Resultssupporting
confidence: 88%
“…In contrast, force measurements between the ceriacoated silicon substrate and the silica particle in DI water resulted in an attractive/adhesive force at pH 4. Abiade et al 28 also showed similar results between a silica probe and ceria thin films at pH 4.5. This attractive force arises from the interaction of a silica surface consisting of negatively charged species with positively charged ceria particles.…”
Section: Afm Force Measurements-mentioning
confidence: 56%
“…The oxygen storage capacity (OSC) and the catalytic activity of ceria are heavily deactivated when it is exposed to high temperatures over 900°C, which is mainly due to thermal sintering [17,18]. As a CMP abrasive, ceria has the inherent disadvantages of an irregular, non-spherical shape and a high specific gravity that cause serious defects (scratches) on the silicon surface [19,20].…”
Section: Introductionmentioning
confidence: 99%